Factors affecting retail sales in small and mid-size cities. Issue 4 (8th August 2018) - Walzer, Norman; Blanke, Andy; Evans, Mim
ABSTRACT: Local public officials and community leaders in small and mid-size cities, especially those in non-metro areas, are facing major decisions regarding their economic future, especially about downtowns and retail businesses. These decisions are complex because of growing competition from internet sales and large retail centers that are undergoing changes as well due to demographic trends that are reshaping buying patterns and approaches. Understanding factors affecting local sales is critical to the future well-being of small communities because sales taxes are often a main revenue source used to finance local services needed to retain and attract residents. This article examines determinants of retail sales in non-metro cities below 50, 000 population to help isolate factors that local policymakers can consider in development strategies. Multivariate regression analyses identify the importance of demographic, economic, locational, and business environment variables on sales. Implications for small and mid-size communities are then discussed.